Process intensification for production of Streptococcus pneumoniae whole‐cell vaccine. Issue 6 (1st March 2020) - Campos, Ivana B.; Cardoso, Celso P.; Fratelli, Fernando; Herd, Muriel; Moffitt, Kristin L.; Lu, Ying‐Jie; Malley, Richard; Leite, Luciana C. C.; Gonçalves, Viviane M.
Abstract: The available pneumococcal conjugate vaccines provide protection against only those serotypes that are included in the vaccine, which leads to a selective pressure and serotype replacement in the population. An alternative low‐cost, safe and serotype‐independent vaccine was developed based on a nonencapsulated pneumococcus strain. This study evaluates process intensification to improve biomass production and shows for the first time the use of perfusion‐batch with cell recycling for bacterial vaccine production. Batch, fed‐batch, and perfusion‐batch were performed at 10 L scale using a complex animal component‐free culture medium. Cells were harvested at the highest optical density, concentrated and washed using microfiltration or centrifugation to compare cell separation methods. Higher biomass was achieved using perfusion‐batch, which removes lactate while retaining cells. The biomass produced in perfusion‐batch would represent at least a fourfold greater number of doses per cultivation than in the previously described batch process. Each strategy yielded similar vaccines in terms of quality as evaluated by western blot and animal immunization assays, indicating that so far, perfusion‐batch is the best strategy for the intensification of pneumococcal whole‐cell vaccine production, as it can be integrated to the cell separation process keeping the same vaccine quality. Abstract : Process intensification to improve biomass was evaluated for production of pneumococcal whole‐cell vaccine. The process intensification was achieved by the integration of the perfusion with the cell separation system, which uses the same space and equipment as batch or fed‐batch, also diminishing the auxiliary time. The perfusion‐batch allowed producing 3‐fold higher biomass than batch and fed‐batch processes. The potential impact of intensification on the quality of the final product was evaluated and no quality differences among the vaccines were observed.